The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.2486/indhealth.43.179
|View full text |Cite
|
Sign up to set email alerts
|

Self-Awakening Prevents Acute Rise in Blood Pressure and Heart Rate at the Time of Awakening in Elderly People

Abstract: Self-awakening, waking up at a designated time decided before sleeping, could prevent failure in the blood circulation vessel system such as heart attack, acute increases in heart rate or blood pressure upon waking. Previous research showed that anticipatory changes occurred in heart rate prior to awakening from a short nap by means of self-awakening for young participants. However, the effects of self-awakening remained unclear for elderly people. The present study examined the effects of self-awakening on he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Rapid secretion of ACTH within the last hour before awakening (when participants anticipate waking up at a predetermined time) 4 and blood pressure/heart rate increases before self‐awakening 5,6 both suggest that self‐awakening facilitates natural awakening and diminishes sleep inertia 3,9 . The present study found that sigma band power gradually decreased before awakening on self‐awakening nights.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Rapid secretion of ACTH within the last hour before awakening (when participants anticipate waking up at a predetermined time) 4 and blood pressure/heart rate increases before self‐awakening 5,6 both suggest that self‐awakening facilitates natural awakening and diminishes sleep inertia 3,9 . The present study found that sigma band power gradually decreased before awakening on self‐awakening nights.…”
Section: Discussionsupporting
confidence: 49%
“…However, the psychophysiological mechanism of self‐awakening remains unknown. The findings that adrenocorticotropin (ACTH) increased 1 h before self‐awakening, 4 and blood pressure and heart rate increased several minutes before self‐awakening, 5,6 suggest that electroencephalogram (EEG) activities would also change before awakening on self‐awakening nights. Tassi et al 7 .…”
Section: Introductionmentioning
confidence: 99%
“…SA enables people to wake up at a predetermined time successfully and accurately and improves morning alertness by eliminating sleep inertia (Ikeda and Hayashi, ), a transitional state from sleep to wakefulness accompanied by incomplete arousal (Tassi and Muzet, ). SA facilitates the transition from sleep to waking at a predetermined waking time by collaborating with inherent sleep–wake regulation, thus coinciding with various physiological changes in vivo , such as increments in serum adrenocorticotrophic concentrations (Born et al ., ), sympathetic activity (Kaida et al ., ), right prefrontal oxygen metabolism (Aritake et al ., ) and a decrement in sigma‐band electroencephalogram (EEG) power (Ikeda and Hayashi, ) in the pre‐awakening period. Sleep inertia varies according to pre‐awakening sleep states, such as the sleep stage (Cavallero and Versace, ), circadian phase (Scheer et al ., ) and residual homeostatic demands (Dinges et al ., ); therefore, when the previous night's sleep is restricted, sleep inertia increases the following morning (Cavallero and Versace, ).…”
Section: Introductionmentioning
confidence: 99%